Deciphering the role of aquaporin 1 in the adaptation of the stinging catfish Heteropneustes fossilis to environmental hypertonicity by molecular dynamics simulation studies. Issue 6 (13th April 2023) - Chutia, Priyambada; Das, Manas; Goswami, Nabajyoti; Choudhury, Manisha; Saha, Nirmalendu; Sarma, Kishore
Abstract: A thorough investigation of the water permeability of H. fossilis aquaporin 1 (hfAQP1) in a hypertonic environment can provide a useful insight into the understanding of the underlying molecular mechanism of its high tolerance to salinity. Here, we constructed a 3 D homology model of hfAQP1 by taking Bos taurus AQP1, AQP0, and human AQP2 as templates using I-TASSER. The model obtained has similar structural organizations with mammalian AQP1s in all aspects. We investigated the water permeability of the modeled hfAQP1 in a 1-palmitoyl-2-oleoyl-sn-glycero-3-phosphocholine (POPC) membrane under neutral and 100 mM hypersalinity by subjecting each system to a 100 ns molecular dynamics simulation. Our results show that hypersalinity hinders water permeation across the membrane through the hfAQP1 channel. A change in the intermolecular distance between key residues of the ar/R selectivity filter along with charge redistribution resulted in the accommodation of only 2–6 water molecules inside the channel at once under hypersaline conditions. We investigated the mRNA expression pattern of hfaqp1 in osmoregulatory organs of H. fossilis in response to 100 mM hypertonicity by using qPCR analysis. The transcript was downregulated in kidney and GI tract, but upregulated in the Gills. Thus, the catfish survive in a hypertonic environment by reducing the transport of water in its cellular systems and downregulating the expression of the hfaqp1 gene. The results observed in our study can shed more light on the functionality of AQP1 in catfishes under salinity stress and aid in future researches on solving more gating mechanisms involved in its regulation. Communicated by Ramaswamy H. Sarma